Вибір оптимального варіанту багатофакторної біометричної автентифікації в інфокомунікаційних мережах - Леонова, Ю. А.; Чеботарьова, Д. В. (ХНУРЕ, 2025)
The paper examines various types of biometric authentication and their features, in particular various methods of static and dynamic biometrics. The current state, development trends and promising areas of application of biometric technologies are analyzed. The most common biometric authentication methods are considered: by face geometry, fingerprint, voice, iris and venous pattern. For these biometric methods, an assessment of quality indicators was performed and a multi-criteria selection of the optimal method was carried out using a set of quality indicators. The optimal method was the method of biometric authentication by venous pattern. Some options for multi-biometric methods were also considered. The optimal method was a method that uses a combination of the following biometric features for user authentication: fingerprint and venous pattern.
Keywords: біометрична автентифікація; biometric authentication